RANCANG BANGUN SISTEM INFORMASI GENERAL APPLICATION BIGETRON E-SPORTS BERBASIS ANDROID - Nabila Rahmarizarti Maharani (2021)
Indonesia is a prosperous country because people can compete and collaborate with people from other countries to promote Indonesia. One of Indonesia's potential in the field of esports can be used to face the demographic bonus. Indonesian e-sports team Bigetron Esports with a red robot logo. Bigetron Red Aliens is a respected name in the highly competitive mobile field of PUBG for gaining world domination after winning the PMCO 2019 championship. The lack of information in an esports team such as biodata of these players and the match schedule for the esports team is a problem that can hinder the growth of the quality of human resources, especially in the field of esports. Based on this, the author built an android-based application to make it easier for bigetron fans to know general information from bigetron e-sports itself. The method used by the author is the Waterfall Method, the Java programming language. The expected result is an android application that can provide general information regarding bigetron e-sports.